2021
DOI: 10.1021/acs.jpcb.1c08666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Symmetry Breaking in Excited Quadrupole Molecules on Transition Dipole Moment

Abstract: Manifestations of charge transfer symmetry breaking in excited quadrupolar molecules in optical spectra are theoretically studied. The molecules are supposed to have π-conjugated structures of A−π−D−π−A or D−π−A−π−D character, where electron acceptors (A) or electron donors (D) are identical. A theory describing the effect of symmetry breaking and solvent fluctuations on the dipole moments of optical transitions associated with absorption by a quadrupolar dye in the ground and excited states, as well as fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…For a three-branched dye like 4 , the oscillator strength should decrease by only one-third. Using a more advanced model of ES-SB, Antipov and Ivanov confirmed such a reduction of the emission dipole moment as electronic excitation localizes …”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 85%
“…For a three-branched dye like 4 , the oscillator strength should decrease by only one-third. Using a more advanced model of ES-SB, Antipov and Ivanov confirmed such a reduction of the emission dipole moment as electronic excitation localizes …”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 85%
“…Multipolar chromophores are known to generate locally excited (LE) states, intramolecular charge transfer (ICT), monomers/dimers, and even symmetry breaking in the excited state facilitated by the surrounding environment. , Resultant characteristics have a significant effect on their linear and nonlinear optical (NLO) properties. For two-photon absorption (2PA), the factors including molecular geometry, intra-/interchromophore orientation, and solvent polarity that affect the relaxation dynamics of excited states have been inspired. , Perylene bisimide derivatives (PBIs) feature the merits of multiple functionalizations and outstanding thermal and photochemical stability, furnishing them suitable for self-assembly processing and impressive optoelectronic applications . Würthner et al reported that PBI aggregation was dominated by electrostatic interactions in nonpolar solvents and by solvophobic interactions in protic solvents. , Meanwhile, extended π-conjugated frameworks with stronger D–A capabilities are likely to enhance the resultant 2PA performance of the PBIs (Figures S1 and S2).…”
Section: Introductionmentioning
confidence: 99%
“…For two-photon absorption (2PA), the factors including molecular geometry, intra-/ interchromophore orientation, and solvent polarity that affect the relaxation dynamics of excited states have been inspired. 3,4 Perylene bisimide derivatives (PBIs) feature the merits of multiple functionalizations and outstanding thermal and photochemical stability, furnishing them suitable for selfassembly processing and impressive optoelectronic applications. 5 Wurthner et al reported that PBI aggregation was dominated by electrostatic interactions in nonpolar solvents and by solvophobic interactions in protic solvents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23,24 Since then, alternative spectroscopic signatures of this process observable by transient electronic absorption or timeresolved fluorescence have also been reported. [25][26][27][28][29] The results obtained so far revealed the crucial role of the environment, which stabilises the symmetry-broken dipolar state relative to the quadrupolar state and compensates for the loss of coupling between the two branches. Therefore, the occurrence of ES-SB depends on a subtle balance between solvation energy and coupling, which are themselves determined by the nature of the D-A subunits and the linker.…”
Section: Introductionmentioning
confidence: 89%